Mill on Conscience: A Sentimentalist Account - Reichlin, Massimo (Filosofia Morale/Moral Philosophy, 2022)
Starting from early contributions, up to the third chapter of Utilitarianism, it is shown that conscience plays a relevant part in Mill’s reworking of the utilitarian moral psychology. His sentimentalistic account of conscience leads Mill to decidedly abandon psychological egoism and to center his ‘proof’ of utilitarianism on the sentiments of unity and fellow feeling that humans acquire in the process of their education. The originality of Mill’s treatment is highlighted, with reference to both his intuitionistic adversaries and to his sentimentalistic forerunners.